Aid effectiveness in fragile and conflict-affected contexts: Lessons from more than two decades of research - David Carment; Yiagadeesen Samy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The objective of this paper is to focus on fragility research findings and examine what works or does not work in development aid and development cooperation in fragile and conflictaffected contexts. We draw on our own research findings as well as country-level studies. We examine questions of aid effectiveness in the context of supporting good governance in fragile states in the first part of the paper. We then consider the impact of COVID-19 and implications for aid effectiveness in fragile states in the second part. In the third and final section we briefly consider how the war in Ukraine is impacting fragile states and the long-term prospects for aid effectiveness in an era of geopolitical rivalry and great power competition.
Keywords: 330; fragile states; fragility; COVID-19; aid effectiveness; Ukraine